Psychological Wellbeing pada Guru Bimbingan dan Konseling: Systematic Review - Amin, Hanun Dzakiyyah; Idriyani, Natris (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Guidance and counselling teachers play a critical role as the front line in delivering counseling services within schools. Accordingly, their psychological wellbeing is a vital factor that must be addressed. This study aims to examine psychological constructs that influence guidance and counseling teachers' wellbeing and to categorize their levels of psychological wellbeing. Utilizing a Systematic Literature Review (SLR) based on the PRISMA framework, incorporating the PICO strategy, and data inclusivity, five relevant empirical studies were analyzed. Findings indicate that emotional intelligence, family social support, self-compassion, self-efficacy, spiritual intelligence, religiosity, and demographic factors (gender and socioeconomic status) positively influence psychological wellbeing. In contrast, the empathy component of personal distress exerts a negative impact. The review also reveals that male guidance and counseling teachers exhibit higher levels of psychological wellbeing compared to their female counterparts, with overall wellbeing levels ranging from moderate to low in two assessed regions. These insights emphasize the need to enhance guidance and counseling teachers' psychological wellbeing by addressing specific contributing factors, thereby improving the quality of guidance and counseling services in schools. Future studies should broaden the scope of psychological constructs examined to further understand the complexities of teacher wellbeing.